Genomics and morphometry of herbarium specimens elucidate the origin of the Cape Verde date palm (Phoenix atlantica A.Chev.) and highlight its agronomic potential - Jerónimo Cid‐Vian; Oscar A. Pérez‐Escobar; William J. Baker; Vincent Bonhomme; Sylvie Ferrand; Sarah Ivorra; Thomas Kaczmarek; Clémence Pagnoux; Jean‐Frédéric Terral; Nathan Wales; Michael D. Purugganan; Simon Creer; et al. (Plants, People, Planet)
Societal Impact Statement As climate change accelerates, breeding resilient crops is urgent. The date palm (Phoenix dactylifera L.), a crucial 18 billion USD fruit crop, underpins North African and West Asian oasis agroecosystems. This study investigates the genetics and morphology of its closest wild relative, the endemic and endangered Cape Verde date palm (Phoenix atlantica A.Chev.). We reveal that the latter originated through a feralisation process from domesticated date palms, evolving back into a wild state with unique genetic diversity. This highlights the need to protect its distinctiveness and opens the possibility of enhancing date palm resilience through its inclusion in breeding programs. Summary The date palm (Phoenix dactylifera L.). is a major crop but its sustainability is threatened by climate change. This challenge could be mitigated by breeding with wild relatives or feral populations. The endangered and endemic Cape Verde date palm (Phoenix atlantica A.Chev.) is thought to be among the closest relatives of the date palm, but its origin and taxonomic status remain unclear, with studies having recovered it either as a separate species or a feral date palm. Better understanding the differentiation of P. atlantica and P. dactylifera is needed to fully unlock the potential of the Cape Verde date palm as a candidate for date palm improvement. In this study, we employ an integrative approach to clarify the origin of P. atlantica. Specifically, we investigate the phylogenetic placement, genetic structure, and seed morphology of P. atlantica by generating extensive genomic and seed morphology datasets from expert‐verified historical and modern specimens of Phoenix, including the type specimen of P. atlantica. Our findings indicate that P. atlantica is monophyletic but nested within P. dactylifera. Its genetic diversity overlaps substantially but not completely with North African date palm varieties, and its seeds share characteristics with those of cultivated and feral date palms, notably elongation, a trait linked to domestication. These results suggest that P. atlantica may be an incipient species that originated from a date palm feralisation event. We emphasise the need for conserving its natural genetic variation and the traditional knowledge associated with its name to support breeding programs.